MPK6‐mediated HY5 phosphorylation regulates light‐induced anthocyanin accumulation in apple fruit. Issue 2 (27th October 2022) - Xing, Yifan; Sun, Wenjing; Sun, Yuying; Li, Jialin; Zhang, Jie; Wu, Ting; Song, Tingting; Yao, Yuncong; Tian, Ji
Summary: Light is known to regulate anthocyanin pigment biosynthesis in plants on several levels, but the significance of protein phosphorylation in light‐induced anthocyanin accumulation needs further investigation. In this study, we investigated the dynamics of the apple fruit phosphoproteome in response to light, using high‐performance liquid chromatography–tandem mass spectrometry analysis. Among the differentially phosphorylated proteins, the bZIP (basic leucine zipper) transcription factor, HY5, which has been identified as an anthocyanin regulator, was rapidly activated by light treatment of the fruit. We hypothesized that phosphorylated MdHY5 may play a role in light‐induced anthocyanin accumulation of apple fruit. Protein interaction and phosphorylation assays showed that mitogen‐activated protein kinase MdMPK6 directly interacted with, and activated, MdHY5 via phosphorylation under light conditions, thereby increasing its stability. Consistent with this finding, the suppression of the mitogen‐activated protein kinase genes MdMPK6 or MdHY5 resulted in an inhibition of anthocyanin accumulation, and further showed that light‐induced anthocyanin accumulation is dependent on MdMPK6 kinase activity, and is required for maximum MdHY5 activity. Under light conditions, active MdMPK6 phosphorylated MdHY5 leading to accumulation of phospho‐MdHY5, which enhanced the binding of MdHY5 to its target anthocyanin related genes in fruit. Our findings reveal an MdMPK6–MdHY5 phosphorylation pathway in light‐induced anthocyanin accumulation, providing new insights into the regulation of light‐induced anthocyanin biosynthesis in apple fruit at both the transcriptional and post‐translational levels.